Akibat Hukum Jual Beli Hak Atas Tanah Adat Yang Dilakukan Tanpa Sepengetahuan Kepala Desa - Hendra Belseran; Jenny Kristiana Matuankotta; Muchtar Anshary Hamid Labetubun (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
Certificate of customary land rights as proof of ownership of customary land rights so that there is overlapping assistance and sale of customary land to other people by several soa/households without the knowledge of the village head so that each of them claims ownership rights to the customary land in question based on customary inheritance law so that detrimental to citizens as buyers. This research is a normative juridical research on this problem and then examines and finds out the answer to this problem through a conceptual approach, statutory approach and case approach, then from the results of this description conclusions and suggestions can be drawn. The research results show that the regulation of buying and selling customary land according to customary law is carried out by the seller as owner communicating with relatives in the Soa/Mata Rumah/Marga to obtain approval in the form of a letter of release of rights to customary land, if there is no Soa/Mata Rumah/Marga approval. then of course the sale and purchase has no validity according to customary law, and it is based on the letter of release of customary land from the Soa/Mata Rumah/Marga that the Village Head as Head of the Traditional Authority issues a letter of release of rights to the customary land that is being sold and bought if it is in accordance with applicable customary law procedures and adhered to by the local Indigenous Community in Moa Lakor District, Southwest Maluku Regency and there are legal consequences for buying and selling rights to customary land without the knowledge of the Village Head, the Indigenous Community, namely the Soa/Mata Rumah/Marga as the owner of the customary land, Village Officials and Elders Customary elders determine attitudes to resolve problems to straighten out the process of buying and selling customary land in accordance with applicable customary law, and if this is not implemented by the seller and the buyer then the customary land object being sold is taken over and controlled by the Soa/Marga/Mata Rumah as legal owner of customary land.